Perceptions of treatment for tics among young people with Tourette syndrome and their parents: a mixed methods study - Cuenca, José (BMC Psychiatry, 2015)
BACKGROUND: Tourette syndrome (TS) among young people is associated with psychosocial difficulties and parents play an important role in the management of the condition. Clinical guidelines have been developed for the treatment of TS and tics, but little is known about how young people and their parents perceive their treatment options or their desired outcomes of treatment. The aim of this study is to explore perceptions of treatments for tics among young people with TS and their parents. METHODS: In-depth interviews with 42 young people with TS and a mixed-methods, online survey of 295 parents of young people with TS. Participant recruitment was conducted through Tourettes Action (TA): a non-profit UK organisation for the support of people with TS. Interview transcripts were analysed using thematic analysis and responses to survey open-ended questions were analysed using content analysis. Triangulation of qualitative and quantitative data from the parents’ survey and qualitative data from the interviews with young people was used to increase the validity and depth of the findings. RESULTS: A strong theme was the perception that health professionals have limited knowledge of TS and its treatment. Medication was a common treatment for tics and both young people and parents described benefits of medication. However, adverse effects were frequently described and these were a common reason for stopping medication among young people. Aripiprazole was viewed most positively. Access to behavioural interventions for tics was limited and 76% of parents wanted this treatment to be available for their child. Some young people had reservations about the effectiveness or practicality of behavioural interventions. Reduction and abolition of tics were desired outcomes of treatment, but both parents and young people also identified the importance of increasing control over tics and reducing anxiety-related symptoms. For young people, managing the urge to tic was an important outcome of treatment. CONCLUSIONS: The results suggest a need for more training in the identification and management of TS and wider availability of behavioural treatments. Clinical trials could explore the effectiveness of Aripiprazole used in combination with psycho-educational interventions to reduce anxiety and promote a sense of control. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-015-0430-0) contains supplementary material, which is available to authorized users.